Benthic macroinvertebrates as bioindicators of water quality in the Vilcanota River, Cusco-Peru - Huamán De La Cruz, Alex (2024)
Macroinvertebrate metrics are excellent tools for assessing water quality due to the sensitivity of biotic and abiotic parameters of their environment. The work aimed to assess the water quality of the Vilcanota River using aquatic macroinvertebrates and biological indices: Andean Biotic Index (ABI), Biological Monitoring Working Party (BMWP) score, and Ephemeroptera, Plecoptera, and Trichoptera (EPT) index. Macroinvertebrates were sampled at four sampling points (P1, P2, P3, and P4) during dry and wet seasons using Surber traps along a 600 m linear transect. In total, 1631 specimens belonging to 04 classes, 11 orders, and 24 families were found. The class Insecta presented the highest values with 1078 specimens (66.1%), six orders (54.5%), and 19 families (79.2%). The evaluation of the water quality of the Vilcanota River showed that the points during the wet season have questionable water quality for the BMWP and ABI indices. In the dry season, most sampling points (except P1, classified as questionable) showed critical water quality in both the BMWP and ABI index. Similarly, the ETP index revealed regular water quality in the wet season, while in the dry season was bad water quality for most sampling (except P2) points.